Implementation of authentication scheme for GNSS signal using mobile phone - Cheng, Kejun (Nanyang Technological University, 2023)
The Global Navigation Satellite System (GNSS) is a vital technology in a multitude of smart devices today. Ensuring the accuracy and authenticity of GNSS signals is crucial for secure positioning and navigation. However, GNSS spoofing attacks pose a significant threat to these systems. This paper focuses on improving the accuracy and user experience of an Android-based GNSS signal authentication application by employing a Navigation Message Authentication (NMA) scheme. Building upon previous work by Yu Han Chu et al. and Neo Zhen Ting et al., this project aims to enhance the existing Android application through error identification, evaluation, and correction, along with user interface enhancements. After implementing the modifications, test results from various environments have shown an improvement in overall accuracy without spoofing signals from around 95% to over 99%.